2017
DOI: 10.1016/j.jdermsci.2017.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus from atopic dermatitis skin alters cytokine production triggered by monocyte-derived Langerhans cell

Abstract: S. aureus TF3378 on AD skin can skew T cell responses via LC toward imbalanced Th1/Th2 skin immunity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 40 publications
2
34
0
1
Order By: Relevance
“…We show that LCs respond to S. aureus with production of a Th1/Th17-polarizing cytokine profile. These data corroborate finding by others, who have demonstrated that LCs internalize S. aureus and subsequently polarize T cells towards Th17 (Igyártó et al, 2011, Kobayashi et al, 2015, van der Aar et al, 2013, Iwamoto et al, 2017. We now elucidate that detection of S. aureus WTA β-GlcNAc is of critical importance for the induced response.…”
Section: Discussionsupporting
confidence: 92%
“…We show that LCs respond to S. aureus with production of a Th1/Th17-polarizing cytokine profile. These data corroborate finding by others, who have demonstrated that LCs internalize S. aureus and subsequently polarize T cells towards Th17 (Igyártó et al, 2011, Kobayashi et al, 2015, van der Aar et al, 2013, Iwamoto et al, 2017. We now elucidate that detection of S. aureus WTA β-GlcNAc is of critical importance for the induced response.…”
Section: Discussionsupporting
confidence: 92%
“…Staphylococcus aureus is the most common cutaneous pathogen capable of evading host defense . S. aureus residing inside human keratinocytes was associated with atopic dermatitis, while S. aureus colonization in chronic diabetic foot ulcers contributes to impaired DNA repair mechanisms, which subsequently serves as a facilitator for the persistent, unresolved inflammatory state found in these wounds .…”
Section: Discussionmentioning
confidence: 99%
“…However, the presence of bacterial infection often impedes wound closure and barrier restoration . Staphylococcus aureus is the most common pathogen causing wound infections and is capable of evading host defense . While S. aureu s is the prevalent pathogen in multiple cutaneous conditions including non‐healing wounds and atopic dermatitis, the mechanisms by which this pathogen persists in skin infection remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…While IL-1 produced by phagocytes is an important cytokine orchestrating host defense against S. aureus , IL-1β is an important proinflammatory cytokine that activates monocytes, macrophages, and neutrophils [39-42]. S. aureus from atopic dermatitis skin can alter cytokine production triggered by monocyte-derived Langerhans cells [43]. …”
Section: Skin Immune Systemmentioning
confidence: 99%